2017
DOI: 10.4102/jtscm.v11i0.332
|View full text |Cite
|
Sign up to set email alerts
|

Equipping small business retailers to manage logistical supply chain drivers: A theoretical guideline

Abstract: Background: Small businesses are seen as the impetus behind a country’s economic growth. The South African government’s continued commitment to prioritise the development of small businesses, the promising rise of the retail sector in South Africa and the substantial contribution of small businesses to trade, business services, personal services and construction make the small retailers a force to be reckoned with. Businesses often fail because of a lack of strategic fit between the competitive and supply chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…With the improvement of people's living standards and dietary structure, dairy products have become an essential nutritional food in people's daily life. Its consumption in the domestic market is also expanding, especially for short-lived dairy products (such as yogurt, fresh agricultural products, and pure milk), showing a rapid growth trend [6]. is not only brings new development opportunities to logistics companies but also brings challenges.…”
Section: Introductionmentioning
confidence: 99%
“…With the improvement of people's living standards and dietary structure, dairy products have become an essential nutritional food in people's daily life. Its consumption in the domestic market is also expanding, especially for short-lived dairy products (such as yogurt, fresh agricultural products, and pure milk), showing a rapid growth trend [6]. is not only brings new development opportunities to logistics companies but also brings challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, South African small business retailers have very little choice but to make use of public transport to move their goods from the wholesalers to their own stores. In order to eliminate these transportation costs there is a need for them to collaborate with each other (Eicker and Cilliers, 2017). Moreover, the author suggested that the savings made from collaboration should be passed to the consumer in order for the South African retailer to gain some competitive edge over the foreign national trader.…”
Section: Challenges and Constraints Facing Small Business Retailersmentioning
confidence: 99%
“…However, the author cautioned that the transportation system in South Africa is inadequate, and small business retailers need to take advantage of the times when traffic is moving freely, such as the late morning. They should use available public transport, such as taxis or trains (Eicker and Cilliers, 2017).…”
Section: Challenges and Constraints Facing Small Business Retailersmentioning
confidence: 99%
“…With the RFID tag, this blood can always know the safety of the blood itself, and can guarantee the safety of blood in real time. 6. The management of medical devices, the re-implantation of used medical devices into the human body is very unethical.…”
Section: Construction Needs Of Safety Medical Networkmentioning
confidence: 99%
“…The World Health Organization survey found that lifestyles affect health by 5 percent. In this context, through health management, self-management is very valuable, can arouse everyone's health awareness, lifestyle changes, and improve people's health [6,7]. However, how to manage the real-time control of personal health information, effectively prevent, and control chronic diseases still faces two challenges.…”
Section: Introductionmentioning
confidence: 99%